Outcomes following stereotactic radiosurgery for small to medium-sized brain metastases are exceptionally dependent upon tumor size and prescribed dose. Issue 2 (28th September 2018) - Moraes, Fabio Y; Winter, Jeff; Atenafu, Eshetu G; Dasgupta, Archya; Raziee, Hamid; Coolens, Catherine; Millar, Barbara-Ann; Laperriere, Normand; Patel, Maitry; Bernstein, Mark; Kongkham, Paul; Zadeh, Gelareh; et al.
Abstract: Background: At our institution, we have historically treated brain metastasis (BM) ≤2 cm in eloquent brain with a radiosurgery (SRS) lower prescription dose (PD) to reduce the risk of radionecrosis (RN). We sought to evaluate the impact of this practice on outcomes. Methods: We analyzed a prospective registry of BM patients treated with SRS between 2008 and 2017. Incidences of local failure (LF) and RN were determined and Cox regression was performed for univariate and multivariate analyses (MVAs). Results: We evaluated 1533 BM ≤2 cm. Median radiographic follow-up post SRS was 12.7 months (1.4–100). Overall, the 2-year incidence of LF was lower for BM treated with PD ≥21 Gy (9.3%) compared with PD ≤15 Gy (19.5%) (sub–hazard ratio, 2.3; 95% CI: 1.4–3.7; P = 0.0006). The 2-year incidence of RN was not significantly higher for the group treated with PD ≥21 Gy (9.5%) compared with the PD ≤15 Gy group (7.5%) ( P = 0.16). MVA demonstrated that PD (≤15 Gy) and tumor size (>1 cm) were significantly correlated ( P < 0.05) with higher rates of LF and RN, respectively. For tumors ≤1 cm, when comparing PD ≤15 Gy with ≥21 Gy, the risks of LF and RN are equivalent. However, for lesions >1 cm, PD ≥21 Gy is associated with a lower incidence of LF without significantly increasing the risk of RN. Conclusion: Our results indicate that rates of LF or RN following SRS for BM are strongly correlated with size and PD. Based on our results, we now, depending upon the clinical context, consider increasing PD to 21 Gy for BM in eloquent brain, excluding the brainstem.